2020
DOI: 10.2147/bctt.s231502
|View full text |Cite
|
Sign up to set email alerts
|

<p>Biomarkers for Inflammatory Breast Cancer: Diagnostic and Therapeutic Utility</p>

Abstract: Inflammatory breast cancer (IBC) is a rare and highly aggressive subtype of advanced breast cancer. The aggressive behavior, resistance to chemotherapy, angiogenesis, and high metastatic potential are key intrinsic characteristics of IBC caused by many specific factors. Pathogenesis and behavior of IBC are closely related to tumor surrounding inflammatory and immune cells, blood vessels, and extracellular matrix, which are all components of the tumor microenvironment (TME). The tumor microenvironment has a cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…It is a relatively infrequent aggressive form of cancer that grows within the dermal lymphatics of breast tissue. It accounts for 1 to 6% of breast cancer in western countries, while its incidence is as high as 10% within the middle East [ 2 , 3 ]. Based on clinical statements, one-third of the affected breast is commonly associated with erythema, edema (orange-peel appearance) and warmness [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a relatively infrequent aggressive form of cancer that grows within the dermal lymphatics of breast tissue. It accounts for 1 to 6% of breast cancer in western countries, while its incidence is as high as 10% within the middle East [ 2 , 3 ]. Based on clinical statements, one-third of the affected breast is commonly associated with erythema, edema (orange-peel appearance) and warmness [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It accounts for 1 to 6% of breast cancer in western countries, while its incidence is as high as 10% within the middle East [ 2 , 3 ]. Based on clinical statements, one-third of the affected breast is commonly associated with erythema, edema (orange-peel appearance) and warmness [ 2 ]. The 5- year overall survival rate of IBC is 55% shorter than that of non-inflammatory breast cancer (non-IBC), with a median survival of 2.9 to 3.8 years[ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…What is the best systemic treatment for newly diagnosed inflammatory breast cancer? A narrative review Tumor -associated macrophages (TAMs) isolated from TME of IBC patients (especially M2 TAMs) produce several cytokines that promote progression and invasion of IBC cells (9,10). Tumor-infiltrating lymphocytes also play an essential role in predictive chemotherapy response (9,10).…”
Section: Review Articlementioning
confidence: 99%
“…Pathological analysis of IBC also shows the hypervascularity, around four times higher than non-IBC vascularity (8). This is consisted with that IBC has higher levels of vascular endothelial growth factor D (VEGF-D), which is an angiogenesis marker (9,10). Several studies reported the different higher mutations in gene expression between IBC and non-IBC, e.g., MYC, PIK3CA, ERBB2 and p53 mutation (11)(12)(13).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation